CORRELATION BETWEEN THE INFUSION OF BETALACTAM ANTIBIOTICS AND THE OCCURRENCE OF PHLEBITIS - Mulia Hakam (Program Studi Ilmu Keperawatan Universitas Jember, 2016)
Effect of infusion is the occurrence of phlebitis, which is characterized by swelling, redness, and pain along the veins. Today, the administration of intravenous therapy (antibiotic administration) is the primary treatment modality. However, it is suggested that the occurrence of phlebitis due to infused antibiotics is more and more increasing. The aimed to identify correlation between the administration infusion of betalactam antibiotics and the occurrence phlebitis at the ward, health care board Jombang. Thisstudy used cross-se ctional design. The population was all patients receiving betalactam